2013
DOI: 10.1155/2013/428542
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Steatosis, Carbohydrate Intake, and Food Quotient in Patients with NAFLD

Abstract: Is steatosis related to the spontaneous carbohydrate intake in patients with NAFLD? We performed dietary records for 24 patients with NAFLD, 3 months after their liver biopsy was performed and before the deliverance of a dietary advice. The food quotient, indicator of the proportion of calories from carbohydrates, was calculated as (1.00×%  calories from carbohydrates/100) + (0.70×%  calories from lipids/100) + (0.81×%  calories from proteins/100). The associations between diet variables and steatosis% on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Other known risk factors of NAFLD are energy intake and BMI. Several previous studies have found that patients with NAFLD tend to have higher energy intake, and a energy-restricted diet was found to have great benefits for weight loss and improving BMI 38–41. However, few studies have considered sedentary time and energy intake at the same time when investigating the association between physical activity and NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Other known risk factors of NAFLD are energy intake and BMI. Several previous studies have found that patients with NAFLD tend to have higher energy intake, and a energy-restricted diet was found to have great benefits for weight loss and improving BMI 38–41. However, few studies have considered sedentary time and energy intake at the same time when investigating the association between physical activity and NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Since high rates of carbohydrate and fat consumption increase insulin resistance and oxidative stress [ 70 ], improving insulin signalling can be achieved by decreasing the intake of carbohydrates and lipids, and attenuating the postprandial hyperlipidemia. This might contribute by decreasing the hepatic cholesterol and FFAs pool required for the de novo lipogenesis process in the liver [ 71 , 72 , 73 ]. The same mechanism was also suggested for acarbose, orlistat and ezetimibe as a prospective treatment for lipid metabolic disorders such as obesity and other insulin resistance complications including NAFLD and diabetes [ 59 , 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…The current opinion is that hypercaloric foods with a high glycemic index induce IR and initialize the steps of liver damage (6,14). However, not only carbohydrates, but all inadequate nutrient intakes may play an important role in the onset and progression of hepatic and metabolic disorders [7,15]. The carbohydrate energy intake could not be considered excessive because it only slightly (17%) exceeded the RDA.…”
Section: Discussionmentioning
confidence: 99%